Corrections to propagators of Quantum Electrodynamics - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The problem of quantum corrections to propagators in Quantum Electrodynamics (QED) is discussed. Methods: The Dyson–Schwinger equation is employed for correcting propagators in QED. Results: The observable quantities in QED are finite. Conclusions: QED divergencies can be avoided by redefining physical quantities in a suitable manner